Image Processing and Communications Challenges 9 9th International Conference, IP&C'2017 Bydgoszcz, Poland, September 2017, Proceedings - Choraś, Michał; Choraś, Ryszard S. (Advances in Intelligent Systems and Computing, 2018)
Presenting a series of research papers on image processing and communications, this book not only provides a summary of currently available technologies but also outlines potential future solutions in these areas. Gathering the proceedings of the 9th International Conference on Image Processing and Communications (IP&C 2017), held in Bydgoszcz, Poland, on September 13-14, 2017, the book is divided into three parts. Part I addresses image processing, offering a comprehensive survey of different methods of image processing and discussing computer vision. In turn, Part II presents novel works in algorithms and methods and showcases formal and practical advances. Lastly, Part III examines networks, communications and a diverse range of applications.